What does Tomas Sodeika teach us? Or the antinomies of the philosophical teaching - Oniščik, Marija (Religija ir kultūra, 2008)
The article is based on the twofold experience of listening to the “living voice” of Tomas Sodeika and reading the corpus of his writings. Some antinomies of philosophical didactics are detected and formulated. Those arise from the reflection on the origin of Western philosophical tradition as a kind of a genealogical tree. The ethical dimension of Greek philosophical education is viewed as a pattern of listening to the teacher speaking and imitating him as a kind of the moral norm or paradeigma. The notion of the philosophical school known from Diogenes Laertius combines the investigation of phenomena and the commitment to certain dogmata, common to the school representatives, these views becoming the obliging rational paradigm of the school. Socratic teaching method exemplified the ambivalence in doing the job of a midwife and that of a sculptor which presupposes the a priori norm of knowledge processed by the teacher. Another set of the antinomies derives form the theory/practice opposition. Here didactics of Thomas Aquinas and Meister Eckhart are the examples of apparent contradiction, since the aim of both is a figure of a preacher proclaiming the law. The Kantian antinomy emerges from the opposition between “historical” and “rational” knowledge, of which only the latter is philosophical in the proper sense, yet it cannot be taught without loosing this property. In Kantian view philosophy and the teacher of philosophy are caught between the idea and the phenomenon. The thesis of performatyvity is presented as the necessary condition of philosophical teaching.
Keywords: philosophical school; teaching; teacher; performatyvity